Using cloud technologies to train future astronomy teachers - I. A. Tkachenko (Academy of Cognitive and Natural Sciences, 2013)
The development of astronomy as a science is characterized by the constant development of modern astronomical research facilities. More and more astronomical equipment is appearing that is controlled remotely. Under such conditions it is not necessary for a researcher to make observations directly, being physically in this or that observatory. It is all the more difficult for a subject teacher to organize this type of class from a purely technical point of view. As a variant, it is enough to have a complex of technical, firmware, program means, systems and the devices functioning on the basis of means of computer equipment, modern means and systems of information exchange providing automation of input, accumulation, storage, processing, transfer and operative management of the information. possibility to use a global information network. Therefore, the ability to work with Internet-technologies, telecommunications, the latest computer technologies becomes a necessary component in the professional training of a modern astronomy teacher.